ANALISIS PERSEPSI MAHASISWA TERHADAP PERSONAL BRANDING GANJAR PRANOWO MELALUI MEDIA SOSIAL TIKTOK MENUJU PEMILIHAN PRESIDEN TAHUN 2024 (Studi Kasus pada Perguruan Tinggi Negeri di Jawa Tengah) - Azmi Muttaqin; , Yulita Nilam Fridiyanti; , Bibit Khoiriyatul Arbain (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
This research aims to analyze student perceptions of Ganjar Pranowo's personal branding via TikTok social media towards the 2024 Presidential Election among State University students in Central Java. Using McNally and Speak theory, this research explores how Ganjar Pranowo utilizes his personal branding strategy to build a strong image and expand the reach of his political messages on TikTok. The content analysis method is used to identify the messages and communication styles used by Ganjar Pranowo in his TikTok content with 7,7 million followers. This research uses descriptive qualitative research methods. Researchers used this method to be able to analyze student perceptions regarding personal branding. Data collection techniques were taken through literature studies, interviews and documentation. This aims to make the data obtained more comprehensive. The research results show that Ganjar Pranowo has succeeded in utilizing authenticity, consistency and follower involvement in strengthening his image. Apart from that, a content strategy that is relevant to issues for students also helps increase its popularity. In general, this research provides insight into how personal branding through social media can be an effective tool in influencing voter opinions and behavior.